The influence of inulin additive in the water composition during the processing of butter - Rashevska, Tamara; Gulyy, Ivan; Bobrovnik, Leonid; Goyko, Iryna (My University, 1998)
The researches of water phase state in butter with inulin additive were carried out. The results stated that inulin additive increased the amount of closely linked adsorptional moisture in butter. The researches of water phase state in butter with inulin additive were carried out. The results stated that inulin additive increased the amount of closely linked adsorptional moisture in butter.
Keywords: butter; inulin; water phase; вершкове масло; інулін; водна фаза; кафедра технології молока і молочних продуктів; кафедра технології оздоровчих продуктів